2015
DOI: 10.18488/journal.2/2015.5.4/2.4.205.218
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Social Capital on Creativity of Employees a Case Study: Productive Firms of Electrical Household Appliances in the North of Iran

Abstract: The general objective of this research is the study of the effect of social capital on creativity of employees of productive firms of electrical household appliances in the north of Iran. The statistical sample of this survey consists of (115) individual of three productive electrical household appliances firms in the north which were selected using convenient sampling method For collecting the data of the survey questionnaire is used. In this research for studying of the hypothesis test, the Partial least squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Thus, personal interactions and networks both within and outside the organisation have significant implication on the creative thinking of an organisation's employees. The results are consistent with Sözbilir (2018), Paramitha and Indarti (2014), Dehnavieh et al (2010) as well as Jamshidi and Kenarsari (2015).…”
Section: Discussion Of Findingssupporting
confidence: 90%
See 2 more Smart Citations
“…Thus, personal interactions and networks both within and outside the organisation have significant implication on the creative thinking of an organisation's employees. The results are consistent with Sözbilir (2018), Paramitha and Indarti (2014), Dehnavieh et al (2010) as well as Jamshidi and Kenarsari (2015).…”
Section: Discussion Of Findingssupporting
confidence: 90%
“…Results indicated that organisational factors had a significant influence on the creativity of the people investigated. Jamshidi and Kenarsari (2015) investigated the effect of social capital on employee creativity. They employed the survey design using a convenient sample of 115 respondents.…”
Section: Social Capital and Creativitymentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that trust among employees is the most basic foundation for interpersonal relations. Trust enhances honesty within the workplace and facilitates the access to the important information (Jamshidi and Kenarsari, 2015). Contrarily to previous research, Chen et al (2007) found when measuring the effect of trust among employees within the research and development (R&D) project teams, that its existence between employees is not a pre-condition for employees’ creativity in R&D project teams.…”
Section: Theory and Hypothesismentioning
confidence: 99%
“…Proper design of social capital can solve the problems that arise from the existence of different social groups within the communities (Bilodeau and White, 2016;Tham-Agyekum and Nimoh, 2013;Evergeti and Zontini, 2006;Jacobs and Tillie, 2004). According to Perkins and Long (2002), "sense of community" is an important dimension of social capital as it expresses the combined effect of networking, reciprocity and trust (Lowea et al, 2016;Sama et al, 2016;Jamshidi and Kenarsari, 2015;De Blasi et al, 2012;Casieri et al, 2010). Immigrants are an organic part of the host society and their integration must be a fundamental concern of societies.…”
Section: Introductionmentioning
confidence: 99%